Stenting Management in Posterior Inferior Cerebellar Artery Aneurysm: A case report - Ahmad Sobri Muda; Amelia Anggia; Anas Tharek; Mohd Fandi Al-Khafiz Kamis; Rajeev Shamsuddin Perisamy; Siow Li Ting; Badrisyah Idris (Journal Of Cardiovascular, Neurovascular & Stroke, 2024)
Posterior inferior cerebellar artery (PICA) distal aneurysm is a relatively rare condition, accounting for 1% or less of all cerebral aneurysms. These aneurysms typically present with neck pain in the posterior cervical and occipital region. Additionally, they may manifest as severe headaches, altered consciousness, lower cranial nerve dysfunction, brainstem compression, or posterior fossa symptoms such as nausea, vomiting, imbalance, or ataxia. CT and MRI are the preferred imaging modalities for identifying and locating the infarct area and detecting other vascular abnormalities. Digital Subtraction Angiography (DSA) is the gold standard for detecting aneurysmal SAH. Endovascular treatment (EVT) has become the primary strategy for managing PICA aneurysms, as it reduces the risk of direct brainstem injury and complications related to anaesthesia.